The College of Radiology Mammogram Subsidy Programme at IIUM Breast Centre, Kuantan : an audit (2004 -2008) - Che Mohamed, Siti Kamariah; Mohamad Mohi, Faraa Hidayah; Abdul Samad Cheung, Humairah; Abdul Rashid, Mohd Amran; Hassan, Radhiana (2009)
INTRODUCTION & OBJECTIVE The IIUM Breast Centre is an accredited mammogram provider under the College of Radiology Subsidised Mammography Programme (CMP) from 2004. We wish to present an audit of the results on 1344 Malaysian women who had mammogram under the programme at the Centre from 2004 - 2008.